What Do Professional Translators Do when Post-Editing for the First Time? First Insight into the Spanish-Basque Language Pair - Aranberri, Nora (HERMES - Journal of Language and Communication in Business, 2017)
Machine translation post-editing is becoming commonplace and professional translators are often faced with this unknown task with little training and support. Given the different translation processes involved during post-editing, research suggests that untrained translators do not necessarily make good post-editors. Besides, the post-editing activity will be largely influenced by numerous aspects related to the technology and texts used. Training material, therefore, will need to be tailored to the particular conditions under which post-editing is bound to happen. In this work, we provide a first attempt to uncover what activity professional translators carry out when working from Spanish into Basque. Our initial analysis reveals that when working with moderate machine translation output post-editing shifts from the task of identifying and fixing errors, to that of “patchwork” where post-editors identify the machine translated elements to reuse and connect them using their own contributions. Data also reveal that they primarily focus on correcting machine translation errors but often fail to restrain themselves from editing correct structures. Both findings have clear implications for training and are a step forward in tailoring sessions specifically for language combinations of moderate quality.